TOLERANSI DAN KERUKUNAN ANTARUMAT BERAGAMA (POLA KOMUNIKASI TOKOH AGAMA DESA ANGGRASMANIS, JENAWI, KARANGANYAR) - Noval Setiawan; Sarbini Sarbini (Academic Journal of Da'wa and Communication, 2020)
The people who live in Anggrasmanis village, consist of various kinds of religions. There are Islam, Christian, and Hinduism. The tolerance between religious communities in Anggrasmanis village was maintained even though it was often tinged with tension and suspicion. This encourages religious figure to build communication. This study aims to describe how the pattern of communication inter-religious figures in Anggrasmanis village, so attitude of tolerance is born. The type of research usedÂ  is a qualitative description method with qualitative approach. Data collection techniques using observation, interviews, and documentation. Researchersâ€™ finding communication patterns of religious figures in Anggrasmanis village are linear communication patterns and circular communication patterns that occur in direct conversation between religious figures and direct feedback. The role of religious figures to building tolerance at Anggrasmanis village is by participating in activities at the village such as religious holidays.